Advances in energy materials and environment engineering Selected, peer reviewed papers from the 2014 International Conference on Energy Materials and Environment Engineering (ICEMEE 2014), October 25-26, 2014, Guangzhou, China - Zhou, Peijiang; Patty, Aragona (Applied Mechanics and Materials, 2015)
Collection of selected, peer reviewed papers from the 2014 International Conference on Energy Materials and Environment Engineering (ICEMEE 2014), October 25-26, 2014, Guangzhou, China